Effects of isokinetic and isotonic muscle training on vertical jumping ability and maximum power output as a result of four and six week training programs - Flick, Bradford Lawrence. (My University, 1983)
This study compared the effects of two training programs, on isotonic and the other isokinetic, on vertical jumping (VJ) ability and maximum power output (MPO) over periods of four and six weeks. Fifty-five male subjects volunteered with 50 completing the six week program. Subjects were randomly assigned to groups and treatments randomly assigned to the three groups. The isokinetic (ISOK) group consisted of N=17, isotonic (IST) N=16, and control (CONT) N=17, subjects. Subjects trained three times per week for six weeks, with training programs consisting of three sets of ten repetitions per workout. Testing was performed initially(T1) at four weeks (T2) and six weeks (T3). Test battery consisted of Margaria-Kalamen power test and jump and reach test for VJ.
Keywords: Jumping; Exercise -- Physiological aspects